North-south collaboration on research and advocacy to reduce armed violence. (1st March 2011) - Pinto, A D; Crespin, E; John, I; Mtonga, R; Valenti, M; Zavala, D
Abstract : Armed violence is a global problem, yet disproportionately impacts certain nations. In recent years, approximately 90% of all direct conflict deaths occurred in low-income countries in Asia, Africa and Latin America. The situation for indirect deaths is even more disproportionate. Further, the South contains almost all countries that are considered to have active conflicts or are post-conflict, related in part to a shared history of colonialism and underdevelopment. Finally, advocates and academics in the South face greater personal risks than those in the North when speaking out against armed violence, particularly if it involves being critical of political forces. Despite this situation, much of the research and advocacy on armed violence originates from universities and organisations in the North. This is particularly the case when looking at funding, leadership and the initiation of projects. This paper will identify best practices of North-South collaborations on armed violence research, education and advocacy. Precedent exists within research, particularly the work of International Physicians for the Prevention of Nuclear War, the Red Cross and other large medical non-governmental organisations. Similarly, best-practice examples of advocacy can be explored that demonstrate effective North-South collaboration. Future work would benefit from a clear definition of partnership, developing broader networks and working towards a South-driven movement. Support should focus on improving Southern access to resources, as identified by these partners. In addition, Northern partners should prioritise examining and changing the role their societies play in sustaining armed violence in the South.